Keratosis pilaris atrophicans faciei with late onset – case report - Purzycka-Bohdan, Dorota; Szczerkowska-Dobosz, Aneta; Nowicki, Roman (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction. Keratosis pilaris atrophicans faciei (KPAF), also known as ulerythema ophryogenes , is a rare hereditary skin disorder of follicular hyperkeratinization. The disease is characterized by erythematous follicular papules on the supraorbital area, cheeks or forehead, with the subsequent gradual loss of eyebrows. Keratosis pilaris atrophicans faciei typically begins in infancy and the progression stops after puberty. Objective . Presentation of a female with onset of KPAF at the age of 34. Case report. A 43-year-old woman was seen in the dermatology outpatient clinic due to cutaneous lesions in the form of small papules located symmetrically on both cheeks and the loss of the lateral one-third of eyebrows. The diagnosis of KPAF was established based on clinical examination. Conclusions . Keratosis pilaris atrophicans faciei is a rare benign disorder and may constitute a diagnostic and therapeutic problem.